Geometry Ability in Contextual Mathematics Learning in Elementary Schools - Sukowati, Berliani Ardelia; Sutama, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: Geometry ability plays a crucial role in contextual learning, especially for elementary school students who are required to solve complex problems. This study aims to: (1) describe the geometry ability of plane and space figures in the context of elementary school learning, and (2) explore how these abilities are manifested in contextual learning settings. Methodology: This research employed a qualitative ethnographic design. The subjects consisted of the school principal, a mathematics teacher, and 17 fifth-grade students at Muhammadiyah Alam Surya Mentari Elementary School. Data collection techniques included interviews, classroom observations, and documentation of students’ test results. To ensure data validity, source and method triangulation were applied. The data analysis followed the flow model involving data collection, reduction, presentation, verification, and conclusion drawing. Results: The study revealed variations in geometry ability among students based on their performance categories. Students in the high category fulfilled all four indicators (M1, M2, M3, and M4). Those in the medium category met three indicators (M1, M2, and M3), while students in the low category only met one indicator (M2). Applications/Originality/Value: The findings highlight the importance of differentiated instruction in teaching geometry through contextual learning. Teachers should consider students’ varying levels of ability when selecting or designing instructional strategies to enhance geometry understanding effectively.